The effect of fabrication methods on the physical properties of Sumberejo kenaf fiber - Polyurethane foam core sandwich composite for sustainable building construction - Ilva Zahrotin; Ariadne L. Juwono; Januar P. Siregar; Seto Roseno; Saeful Rohman; Eryanti Kalembang (Results in Materials)
Sandwich composites made of natural fibers are currently being investigated for use in buildings. Kenaf fiber is an environmentally friendly material that is widely used in cement and polymer composites owing to its strength and support. The purpose of this study was to investigate the fabrication method and physical properties of a Sumberejo kenaf fiber-polyurethane foam core sandwich composite (KF/EP-PU foam) for sustainable building construction. Sumberejo kenaf/epoxy laminate composites (KF/EP) were used as the skin layer in sandwich composites, with polyurethane foam (PU foam) as the core of the sandwich composites. Sandwich composites were fabricated using two methods: cold press and vacuum-assisted resin infusion (VARI). The water absorption, burning rate, and sound absorption coefficient of the sandwich composite production process were investigated. The results demonstrated that sandwich composites employing the VARI method had a lower percentage of water absorption (3.95 ± 0.38 %) than cold press method (7.21 ± 0.67 %). This indicates a more effective epoxy resin wetting procedure for covering the kenaf and polyurethane foam. The horizontal burning test showed no significant difference between the KF/EP-PU foam VARI (18.5 ± 1.3 mm/min) and KF/EP-PU foam cold press (18.9 ± 0.4 mm/min). The highest peak sound absorption coefficient of the KF/EP-PU foam cold press was 0.168 at 1000 Hz, whereas KF/EP-PU foam VARI sample had a sound absorption coefficient of 0.169 at 1128 Hz. It is recommended to consider the use of suitable fabrication methods for building application. The fiber and matrix weight fractions also need to be explored further.